Analysis of Corrosion on Flow Line Pipe LR 038 Gathering Station PT. Pertamina Hulu Rokan Zone 1 Lirik Field - Masnur, Dedy; Rahmadiza, Duta (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Riau, 2024)
PT. PERTAMINA Hulu Rokan Zone 1 Field Lirik is engaged in upstream activities including exploitation and production, with two districts producing 2,000 barrels per day. An important component in oil production is the pipeline network, which distributes various fluids suchas water, gas, and oil. This study assesses the remaining effective life of the LR 038 pipeline network and provides preventive recommendations to avoid damage to the pipeline network, thus optimizing oil processing operations and maintaining material integrity using direct observation and inspection methods in the field. The results obtained are the remaining pipe life of 19.9 years with a corrosion rate of 0.003 in years. Recommendations for periodic painting and inspection.